Gram-Scale Synthesis of Substituted Triarylmethanes - Chang, Meng-Yang; Lin, Chun-Yi; Chen, Shin-Mei (Synthesis, 2022)
A high-yield, open-vessel route for the facile-operational, gram-scale synthesis of functionalized triarylmethanes (TRAMs) is described via silica-coated magnetic nanoparticles of modified polyphosphoric acid (NiFe2O4@SiO2-PPA)-mediated intermolecular Friedel–Crafts reaction of substituted aryl aldehydes with 2 equivalents of oxygenated arenes under environmentally friendly reaction conditions. Among the overall reaction process, only water was generated as the by-product. Various reaction conditions are investigated for efficient transformation.
Keywords: gram-scale synthesis; triarylmethanes; magnetic nanoparticles; Friedel–Crafts reaction; environmentally friendly